A utilização do método peer instruction em aulas de matemática no ensino médio - Ravera, Tercio Costalonga (2019)
Students' difficulties in learning math subjects are notorious for many teachers in the field. In order to reduce these difficulties, researchers have developed teaching proposals that help the teacher to make the content more attractive to learners, promoting debates, dialogues and class participation. However, based on research that reveals the rate of students with problems learning mathematics, we can see that. The volume of publications in the area is low in relation to the need for research. Therefore, this research was carried out with the active methodology Peer Instruction, coming from the area of Physics teaching and little known in Brazilian journals for the process of teaching and learning in Mathematics. Thus, the objective of this research was to use and evaluate the active methodology Instruction by Colleagues, applying it in the contents of the first grade of high school, aiming to analyze its contribution to the process of teaching and learning in Mathematics, as well as its viability. and use in the classroom. The research was carried out at the President Getulio Vargas State School of Elementary and High School, located in Cachoeiro de Itapemirim, with first grade students and were worked with percentage content and simple interest, bringing positive results that suggest new method implementations.